Fatigue of shulder's internal rotators following a 200-m all-out swim - Dekerle, J.; King, L. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
A high prevalence of shoulder pain has been reported for competitive swimmers with severe cases potentially leading to functional impairments and termination of participation (Tate et al. 2012). Greater swimming exposure defined by distance or time spent swimming, characterises symptomatic groups (Tate et al. 2012; Sein et al. 2010) who present, among other physical impairments, weakness of the internal and external rotation strength (Tate et al. 2012; Beach et al. 1992; Se in et al. 2010). Pain vs pain-free swimmers, and within the pain group, symptomatic vs non symptomatic shoulders, are characterised by reduced concentric and eccentric internal rotational torques leading to greater external-to-internal rotational strength ratios (Bak and Magnusson 1997). Muscle fatigue of the internal rotators and the pectoralis major in particular, affects dynamic stabilisation of the humeral head which may lead to microtrauma (Wanivenhaus et al. 2012). During the arm stroke in freestyle, the overhead arm action is produced by the scapular and rotator cuff muscles. These muscles work in synergy to deliver movement whilst establishing stability (McMaster 1999). Shoulders are internally rotated during the hand entry, late pull-through phase (90° flexion to hand exit) and recovery phase, i.e. all but one phase of the stroke [early pull-through phase (Wanivenhaus et al. 2012)]. Studies measuring electromyographic responses during all-out front crawl swimming have reported increases in activities of upper-limb muscles including internal rotators such as the pectoralis major as fatigue developed (Rouard 2010; lkuta et al. 2012; Figueiredo et al. 2013). This was suggested to reflect the recruitment of additional motor units in an attempt to maintain the swimming speed (Rouard 2010). Most investigations on muscular strength and endurance report the use of isokinetic dynamometers to ensure validity and reliability in torque measurement (Baltzopoulos and Brodie 1989). Torque can be measured during short voluntary contractions performed (a) maximally (MVC) and {b) at different, set (isometric), joint angles. Pre- and post-exercise measurements allow for the maximal torquejoint angle relationship to be assessed in both fresh and fatigued states of muscle groups [human elbow flexors, (Philippou et al. 2004; Prasartwuth et al. 2006)1. Fatigue has been shown to alter the inverse-U shape of this relationship with a shift to the right of the optimal joint angle alongside a fatigue-reduced peak torque (Philippou et al. 2004; Prasartwuth et al. 2006). Decrements in force production have been observed during or following all-out swimming (Aujouannet al. 2006; Rouard 2010). To our knowledge, no study has reported the effect of a fatiguing swim on the ability for a muscle group, the internal rotators in the present study, to generate force across a range of joint angles. A significant decline would ascertain the presence of fatigue (Taylor & Gandevia 2008). Muscular fatigue has often been put forward as the main explanatory mechanism underpinning the changes in the stroking parameters observed during a 200-m all-out swim (Aiberty et al. 2005; Figueiredo et al. 2013). The aim of this study was therefore to quantify the loss of isometric torque during MVCs performed prior and following a 200-m all-out swim. Three different joint angles for the internal rotators were tested. Changes in swimming speed, stroke rate and stroke length were also quantified throughout the 200-m all-out swim. lt was hypothesised that maximal isometric torque would be reduced post-exercise. This evidence of fatigue should be concomitant with a reduction in speed, stroke length and stroke rate during the 200-m swim.